Maintaining optimal cardiovascular health metrics and carotid intima-media thickness among Korean adolescents - Kaneko, Fumie; Lee, Hokyou; Shim, Jee-Seon; Kim, Hyeon Chang (Clinical hypertension, 2025)
The distribution of cardiovascular health (CVH) and its association with vascular health among Asian adolescents is understudied. We examined the distribution of optimal CVH metrics and their association with carotid intima-media thickness (cIMT) in Korean adolescents. We analyzed data from a cohort of 694 healthy Korean adolescents with an average follow-up period of 2.4 years. CVH scores were assessed at baseline and follow-up using 6 metrics from Life's Essential 8 (LE8), excluding diet and sleep. Additionally, we developed an experimental set of 7 metrics by incorporating a psychological health indicator. We examined the association between CVH and cIMT using 2 approaches: 1) aggregated CVH, calculated as the average of the 2 time points, and 2) changes in CVH over time. High cIMT, defined as the highest sex-specific quartile measured at the follow-up visit, was analyzed using multivariable logistic regression. Among participants (mean age, 15.9 years at baseline), approximately 25% maintained an optimal-level CVH, with physical activity being the most challenging metric. Higher CVH was associated with lower odds of high cIMT; gradually decreasing odds according to higher aggregated CVH were evident. Maintaining optimal CVH resulted in 50% lower odds of high cIMT compared to those with persistently suboptimal CVH. The results remained consistent when the psychological health metric was incorporated into CVH. Among Korean adolescents, CVH scores for 6 of LE8 metrics, excluding diet and sleep, were comparable to those of non-Hispanic Asian adolescents in the U.S. Higher CVH was associated with lower odds of high cIMT at age 18.